UJI PROFIL FITOKIMIA, KAPASITAS ANTIOKSIDAN, DAN TOKSISITAS EKSTRAK METANOL DAUN TAPAK LIMAN (Elephantopus scaber L.) - Hartono, Daniswara Aliya; Hendrawan, Siufui; Ferdinal, Frans (FKIP Universitas Tanjungpura, 2025)
Exposure to environmental pollutants leads to the accumulation of free radicals, overbalancing endogenous antioxidant, and exacerbating oxidative stress level within the body. Oxidative stress is one of primary factors causing numerous health issues, such as aging, cardiovascular, and neurodegenerative disorders, highlighting the need for additional antioxidant supplementation. Elephantopus scaber L., known as tapak liman, is a medicinal plant traditionally utilized to manage diseases, including malaria, anemia, and skin infections. However, its potential as an antioxidant supplement remains underexplored. This research investigates the methanol extract of tapak liman leaves, evaluating its phytochemical content, antioxidant activity, and toxicity. Phytochemical screening identified various secondary metabolites, such as of alkaloids, flavonoids, cardiac glycosides, coumarins, phenolics, quinones, betacyanins, tannins, and saponins. Total phenolic content was found at 17,22 ± 0,15 mg GAE/g. Antioxidant capacity was assessed using ABTS (2,2-azinobis-3-etilbenzotiazolin-6-sulfonat) and FRAP (Ferric Reducing Antioxidant Power) assays, resulting IC50 values of 18,78 µg/mL and 19,26 µg/mL, respectively. These values indicated very strong antioxidant activity, slightly higher than those of Trolox® as a vitamin E analog, which showed IC50 values of 13,27 µg/mL (ABTS) and 10,42 µg/mL (FRAP). Toxicity evaluation through brine shrimp lethality test displayed an LC50 of 394,54 µg/mL, indicating moderate toxicity and potential antimitotic activity, which may correlate with anticancer properties. Owing to its vast bioactive components and strong antioxidant capacity, tapak liman leaf extract demonstrates potential as a safe and effective natural antioxidant agent for further development.